Toward a Bijural Interpretation of the Principle of Respect in Aboriginal Law - Manley-Casimir, Kirsten (McGill Law Journal / Revue de droit de McGill, 2016)
Aboriginal law disputes are disputes that arise in the spaces between Indigenous and non-Indigenous societies. To date, the Supreme Court of Canada has resolved Aboriginal law disputes under section 35 by relying heavily on the common law to the exclusion of Indigenous legal traditions and principles. In this article, the author argues that applying a bijural interpretation of the principle of respect provides a promising pathway forward in resolving Aboriginal law disputes in a way that supports the grand purpose of section 35 of the Constitution Act, 1982—reconciliation. The author discusses the principle of respect by considering both non-Indigenous and Indigenous theories to propose a robust conception of respect to guide Aboriginal law jurisprudence. She then suggests three ways to implement the principle of respect in the intercultural relationship: (1) making interdependence and relationships primary; (2) rejecting colonial attitudes and stereotypes of Indigenous peoples; and (3) creating political and legal space for the expression and flourishing of cultural difference.